Removal of Cu2+ from wastewater by modified xanthan gum (XG) with ethylenediamine (EDA). Issue 86 (2nd September 2016) - Qiu, Haiyan; Yan, Junhua; Lan, Guihong; Liu, Yongqiang; Song, Xiaoqin; Peng, Wanxi; Cui, Yingyi
Abstract : Herein, a new adsorbent was synthesized by modifying xanthan gum for the removal of Cu 2+ from wastewater. Abstract : Herein, a new adsorbent was synthesized by modifying xanthan gum for the removal of Cu 2+ from wastewater. Xanthan gum was first successfully modified with thionyl chloride followed by ethylenediamine. The modified xanthan gum was characterized via Fourier transform infrared spectrometry (FTIR), carbon nuclear magnetic resonance ( 13 C NMR), scanning electron microscopy (SEM), energy dispersion spectroscopy (EDS) and thermogravimetry (TG) for a better understanding of its Cu 2+ removal efficiency. In addition, the effects of pH, contact time, adsorbent dosage, initial concentration of Cu 2+ and coexisting ions on the adsorption of Cu 2+ were investigated via batch adsorption studies. Results suggest that the adsorption process of Cu 2+ follows a pseudo second order kinetics model with an equilibrium time of 120 min. The experimental data could be fitted with the Langmuir isotherm better than the Freundlich model. The adsorption capacity of Cu 2+ by the modified xanthan gum reached up to 46.95 (mg g −1 ). The adsorbent could be easily regenerated by only the addition of 0.1 M HCl. Also, the adsorption effect of other divalent cations by XG-NH2 was preliminarily investigated.